SOSIALISASI PENGELOLAHAN DANA BANTUAN OPERASIONAL SEKOLAH DI SMA LAB SCHOOL UNIVERSITAS TADULAKO PALU - Masruddin Masruddin; M. Ikbal A; Sugianto Sugianto; Josua Gabriel Galamba (LPPM Universitas Bina Bangsa, 2022)
School Operational Assistance Fund, hereinafter referred to as the BOS Fund, is a fund used primarily to fund non-personnel expenditures for primary and secondary education units as implementers of compulsory education programs, and it may be possible to fund several other activities in accordance with the provisions of laws and regulations. Technical instructions (juknis) regarding the management of regular BOS Funds are regulated in Permendikbudristek Number 2 of 2022. The approach taken in the implementation of service activities is through socialization of the calculation of Tax Funds for school operational assistance in accordance with government regulations. The goal is that the management of the BOS funds can be understood by the school. In addition to the presentation, dialogue is also carried out. Through a dialogue approach, the communication that occurs will be two-way. So it is hoped that the team will be able to know more about the problems or obstacles faced by school managers. The target of this service is the transfer of knowledge possessed by the service team in the accounting field, especially the school to the BOS fund manager. So that they are expected to be able to manage operations well